Start-up characteristics of MEMS-based micro oscillating heat pipe with and without bubble nucleation - Sun, Qin; Qu, Jian; Yuan, Jianping; Wang, Hai (International journal of heat and mass transfer, 2018)
•High speed visualization on the start-up behavior of micro-OHP was experimentally performed.•Start-up with and without bubble nucleation (STWBN/STWOBN) were observed.•The average evaporator temperature could be even above 140 °C for the STWBN mode.•We propounded a theoretical model to predict the average evaporator temperature at the STWBN mode. The startup characteristics of micro oscillating heat pipe (micro-OHP) have been experimentally investigated using a high-speed CCD camera in conjunction with the temperature measurement. The micro-OHP was fabricated on a silicon wafer by the MEMS technology, having trapezoidal channels with a hydraulic diameter of 357 μm. HFE-7100 was used as the working fluid with volumetric filling ratios ranging from 31% to 72%. The effects of filling ratio and heating power input on the start-up process were presented. Two different start-up behaviors, so-called start-up with and without bubble nucleation (STWBN/STWOBN), subject to different heat input levels were observed, and the underlying mechanisms were elaborately analyzed. The occurrence of STWBN or STWOBN depends mostly upon the spatial distribution of slugs/plugs in the micro-OHP. For the STWOBN mode, the fluid movement could be triggered by intense liquid film evaporation without nucleation with evaporator temperature less than 80 °C. However, the STWBN mode is sometimes indispensable to excite the two-phase oscillations in the micro-OHP due to the non-desirable slug/plug distribution, leading to much higher evaporator temperatures even greater than 140 °C to initiate the bubble generation. To predict the startup temperature at the STWBN mode, a theoretical model to describe the wall superheat required for incipient bubble nucleation in microchannels was propounded and largely agreed with the present experimental data. Micro-OHPs worked at the STWBN mode may greatly hinder their applications in electronics cooling, and artificial cavities fabricated or embedded on silicon channel wall surfaces are proposed to facilitate bubble nucleation and then the startup at low temperatures.